PENGARUH PENDEKATAN JOYFUL LEARNING BERBASIS AUGMETED REALITY TERHADAP KECEMASAN MATEMATIKA SISWA: SYSTEMATIC LITERATURE REVIEW - Izatunnisa; Nindiasari, Hepsi; Fathurrohman, Maman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effect of a joyful learning approach based on augmented reality on students' mathematics anxiety through a systematic literature review (SLR) method. Literature searches were conducted systematically using the keywords "augmented reality in mathematics learning", "joyful learning mathematics", and "mathematics anxiety" across various online scientific journal databases, including Google Scholar, Garuda, Scopus, and Sinta Kemdiktisaintek, covering nationally indexed journals (Sinta 2–Sinta 4) and reputable international journals published between 2020 and 2025. Based on the application of inclusion and exclusion criteria using the PRISMA method, which includes the stages of identification, screening, eligibility, and included, a total of 6 relevant articles were obtained, with research subjects predominantly consisting of junior and senior high school students. The findings indicate that augmented reality helps visualize abstract concepts, thereby facilitating students' understanding, while joyful learning creates an enjoyable learning atmosphere and reduces academic pressure. The integration of both approaches has been proven to enhance motivation and self-confidence as well as significantly reduce mathematics anxiety, making this approach a potentially effective and innovative learning strategy for improving the quality of mathematics education.